Impact of argon flow and pressure on the trapping behavior of nanoparticles inside a gas aggregation source. Issue 1 (19th October 2021) - Drewes, Jonas; Ali‐Ogly, Suren; Strunskus, Thomas; Polonskyi, Oleksandr; Biederman, Hynek; Faupel, Franz; Vahl, Alexander
Abstract: In this study, in situ UV–Vis spectroscopy is used to investigate the growth and transport of nanoparticles inside a gas aggregation source (GAS) dependent on the Ar gas flow and operating pressure. It was found that the nanoparticles were becoming trapped at different positions inside the GAS dependent on the gas flow. Moreover, in situ UV–Vis spectroscopy suggested the presence of large nanoparticles inside the GAS, which were not observed outside. Computational fluid dynamic simulations were performed to study the velocity distribution inside the GAS. Three distinct areas were identified, where nanoparticles can become trapped or lost. The gas flow velocity distribution was found to strongly impact the transport of nanoparticles. Abstract : Trapping of nanoparticles inside a gas aggregation source was studied by in situ UV–Vis measurements. Three distinct trapping regions are identified by computational fluid dynamic simulations, which revealed the gas velocity pattern. The positions of the trapping regions are impacted by argon gas flow and the resulting pressure. The gas velocity pattern determines the transport of nanoparticles and hence is identified as a crucial parameter for the design of future gas aggregation cluster sources.